2020
DOI: 10.1017/s1368980020004176
|View full text |Cite
|
Sign up to set email alerts
|

The idealisation of bottle feeding: content analysis of feeding bottles and teats packages in Uruguay

Abstract: Objective: The information displayed on the packages of feeding bottles and teats commercialized in Montevideo (Uruguay) was analyzed using content analysis with the goal of identifying key marketing practices that may discourage breastfeeding. Design: The study was conducted as part of the periodic assessment performed by the Uruguayan government to monitor the marketing of breast-milk substitutes. All the feeding bottles and teats sold in 44 retail outlets selling breast-milk substitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…These marketing cues can be defined as any textual or visual element of the labels that may create an idealized image of the use of human-milk substitutes or the belief that they are equivalent or superior to human-milk (WHO & UNICEF, 2017b). Similar results have been recently reported for the labels of other products included in IC, like foods targeted at infants and young children, feeding bottles and teats (Alcaire et al, 2020;Karageuzián et al, 2021;Pomeranz et al, 2018).…”
supporting
confidence: 89%
“…These marketing cues can be defined as any textual or visual element of the labels that may create an idealized image of the use of human-milk substitutes or the belief that they are equivalent or superior to human-milk (WHO & UNICEF, 2017b). Similar results have been recently reported for the labels of other products included in IC, like foods targeted at infants and young children, feeding bottles and teats (Alcaire et al, 2020;Karageuzián et al, 2021;Pomeranz et al, 2018).…”
supporting
confidence: 89%
“…Some examples included a study examining nine companies in 14 countries (Burkina Faso, Canada, China, India, Indonesia, Kenya, Laos, Malaysia, Myanmar, Pakistan, Singapore, The Philippines, United States, and Vietnam; Ching et al, 2021) and another carried out in four countries (Cambodia, Nepal, Senegal, and Tanzania; Sweet et al, 2016), which found explicit invitations on the packaging to interact with the manufacturer's “nutrition experts” or join a baby club for special offers (Ching et al, 2021; Sweet et al, 2016). Similar branding used across products for different ages was found in Nepal (Pries et al, 2016), and a lack of information about risks from improper use was reported in Uruguay (Alcaire et al, 2020). In a study in Ecuador, more than half of the BMS labels contained texts or images that idealized their use (Caicedo‐Borrás et al, 2021).…”
Section: Resultsmentioning
confidence: 79%
“…Promotion via nutrition and health claims was reported in 66 studies, including statements making claims to benefit child health and development from Cambodia and Nepal (Champeny et al, 2019) and from a multi‐country study in Europe (Austria, Bulgaria, Hungary, and Israel; WHO Regional Office for Europe, 2019a), to help with digestion, support for cognitive development and aid to the immune system in an Australian study (Berry & Gribble, 2017). Promotion of feeding bottles and teats also included claims such as “proven to reduce colic” reported in Uruguay (Alcaire et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations